With or Against the People? The Impact of a Bottom-Up Approach on Tax Morale and the Shadow Economy - Benno Torgler; Friedrich Schneider; Christoph A. Schaltegger (Center for Research in Economics, Management and the Arts (CREMA), 2007)
Policymakers often propose strict enforcement strategies to fight the shadow economy and to increase tax morale. However, there is also a bottom-up approach: decentralizing the political power to those who are close to the problems and give them a direct political say. This paper analyses the impact of direct democracy and local autonomy on tax morale and the size of the shadow economy. We use two different data sets on tax morale at the individual level (World Values Survey and International Social Survey Programme), and macro data of the size of the shadow economy to systematically analyse the effects of institutions in Switzerland, a country where participation rights and the degree of federalism vary across different cantons. The findings suggest that direct democratic rights and local autonomy, have a significantly positive effect on tax morale and the size of the shadow economy.
Keywords: H26; H73; D70; 330; Tax Morale; Shadow Economy; Tax Compliance; Tax Evasion; Direct Democracy; Local Autonomy